DAMPAK CORPORATE SOCIAL RESPONSIBILITY PT. UPC SIDRAP BAYU ENERGI TERHADAP PENINGKATAN KESEJAHTERAAN MASYARAKAT DI KABUPATEN SIDENRENG RAPPANG - Widodo, Uun Purwati; Semaun, Syahriyah; Aminah, Sitti; Bahri. S, Andi; Nurhayati, St. (Transpublika Publisher, 2024)
Community empowerment is one of the efforts made to improve community welfare. This effort can be carried out through various approaches, one of which is Corporate Social Responsibility (CSR), a program that focuses on community and environmental empowerment as a form of social responsibility for companies located in a region. This research aims to determine the impact of Corporate Social Responsibility (CSR) programs implemented by PT UPC Sidrap Bayu Energi in improving community welfare in Sidenreng Rappang Regency. This is qualitative research with a field research approach to observe the impact of PT UPC Sidrap Bayu Energi's Corporate Social Responsibility (CSR) program on community welfare in Sidenreng Rappang Regency. The data in the research were collected through interviews with PT UPC Sidrap Bayu Energi and residents in Pabberesseng Hamlet as beneficiaries. The results of this research indicate that the Corporate Social Responsibility (CSR) program implemented by PT UPC Sidrap Bayu Energi succeeded in achieving 85% of their goal and provided significant benefits to the community in Sidenreng Rappang Regency. CSR programs such as providing clean water, solar electricity, road repairs, playground construction, and school sanitation have contributed to improving the health, economic productivity, and quality of life of the community.